Wolf predation in the Burwash caribou herd, southwest Yukon - Gauthier, David A.; Theberge, John B. (Rangifer, 1986)
The role of wolf predation as a proximate mortality factor influencing caribou herd growth was assessed in the Burwash herd (400 animals) in the southwest Yukon between 1980 - 1982. Ten to 14 wolves in two packs preyed primarily on caribou (Rangifer tarandus caribou) and moose (Alces alces) with disproportionate consumption of caribou (relative to available biomass) in the rut and winter periods. Wolf predation was responsible for 72% of total annual mortality in 1980 - 1981 and 46% in 1981 - 1982. Losses due to human harvest varied between 7 to 13%. Additional limited data on climatic factors and winter forage indicated forage-climate were not major proximate mortality factors in 1980 - 1981, but that early-calving climate may have been a factor in increased calf mortality in 1982.